Dirt bands in the bare ice area around the Sor Rondane Mountains in Queen Maud Land, Antarctica - Hiroshi Naraoka; Keizo Yanai; Shuji Fujita (National Institute of Polar Research, 1991)
Dirt bands were observed on the surface of the bare ice fields around the SΦr Rondane Mountains during the search for Antarctic meteorites in 1988-1989. Dirt bands were commonly distributed on the bare ice around the mountains, especially in Nansenisen. Dirt bands were collected and filtered after melting. Microscopic observation revealed that dust materials were composed mainly of volcanic glass shards. Five types of volcanic ash were preliminarily clarified with respect to the colors (black, dark gray, gray, reddish brown and pale gray) and sizes (5-50μm) of the particles. The EPMA chemical analyses indicated that the volcanic glass shards contained 50-70% SiO_2 and belonged to the nonalkaline region considering from the SiO_2-(Na_2O+K_2O) diagram.